E GAMBARAN KETEPATAN KUNJUNGAN K1 PADA IBU HAMIL - Eva Nurlaela; sri Rahayu (Fakultas Ilmu Kesehatan Unsika, 2022)
Adolescence is a period of transition from childhood to adulthood characterized by physical and psychological changes. According to a World Health Organization (WHO) survey in several countries, adolescent females aged10-14 years have problems with reproduction. In Indonesia, out of 43,3 adolescent females aged 10-14 years behave very badly in hygiene. Based on the initial survey conducted at Middle School 3 Trimurjo of Central Lampung Regency, of the 30 students of VII & VIII grades interviewed 4 people who understand how to do vulva hygiene treatment while 26 people pay less attention to vulva hygiene during menstruation. This research type is quantitative with a cross-sectional survey design. The population of this study was all students in VII and VIII grades who have menstruated and are willing to be respondents at Middle School 3 Trimurjo of Central Lampung Regency amounting to 52 respondents. This research sample was all students of VII and VIII grades who are present during the research implementation. The analysis used was the chi-square test. The research result showed that there was a correlation between reproductive health knowledge with the hygiene behavior of adolescent females when menstruation at the Middle School 3 Trimurjo of Central Lampung Regency in 2021 with a p-value: of 0.008 and OR 9.0. As a suggestion, the health workers' role needs to be improved in providing education through scheduled and on going counseling to adolescents in educational institutions. Keywords : Reproductive Health, Menstruation, Hygiene Behavior